Graphene nanoparticle-embedded PANI-PPy hybrid nanocomposite for high-performance symmetric supercapacitor application - Khairul S.I.; Ansari M.N.M.; Duraisamy E.; Elumalai P.; Thomas P. (Elsevier Ltd, 2023)
Aniline; Capacitance; Cyclic voltammetry; Electric discharges; Electrochemical electrodes; Electrolytes; Molar ratio; Nanocomposites; Nanoparticles; Polymer matrix composites; Polypyrroles; Scanning electron microscopy; Sulfur compounds; Supercapacitor; EDLC; Electrode material; Hybrid nanocomposites; Oxidative polymerization; Oxidizing agents; PANI; Performance; Polyaniline/polypyrrole; Supercapacitor application; Symmetrics; Graphene